Experimental Investigation of the Spiral Structure of a Magnetic Capsule Endoscope. (2nd June 2016) - Yang, Wanan; Li, Zhen; He, Yong; Dai, Houde; Wu, Zhouxing
Fitting a wireless capsule endoscope (WCE) with a navigation feature can maximize its functional benefits. The rotation of a spiral-type capsule can be converted to translational motion. The study investigated how the spiral structure and rotational speed affected the capsule's translation speed. A hand-held instrument, including two permanent magnets, a stepper motor, a controller and a power supplier, were designed to generate rotational magnetic fields. The surfaces of custom-built permanent magnet rings magnetized radially were mounted in spiral lines with different lead angles and diameters, acting as mock-up capsules. The experimental results demonstrate that the rotational speed of the magnetic field and the spiral have significant effects on the translational speed of a capsule. The spiral line with a larger lead angle and the rotating magnetic field with a higher speed can change the capsule's rotation into a translational motion more efficiently in the intestine.